Paisagem urbana, morfologia e arquitetura doméstica portuense: a urbanização do Campo do Cirne no século XIX - Rocha, Manuel Joaquim Moreira da (2018)
Since the middle of the 19th century the city of Porto lives a period of strong urban dynamism. The citygains a new configuration, occupying the more peripheral zones away from the old city nucleus which wereidentified in the development plan of the Almadas. The urbanization of Campo do Cirne (Quinta de Reimão),located in the eastern part of the city, will take place from 1882 onwards. The construction of the railway station in the eastern part of the city, inaugurated in 1875, was a stimulus for the valorization of this area. The planning of the new streets in Porto followed a vanguard plan in Portugal.The urbanization plan of Campo do Cirne reveals knowledge regarding what was being done in Paris andBarcelona, under the proposals of Georges Haussman and Illfons Cerdà. The urban plan of Campo do Cirne wasorganized from a semi-circular square, where the main arteries started; these arteries were crossed by severalstreets, according to an orthogonal plane. In the urbanization plan of Campo do Cirne, the streets for this newarea of the city were defined, as well as models of elevations for the houses to be built in each of the arteries.Campo do Cirne is a good example of how Porto and the organisms that managed it were sticking to thebest international practices of urban landscape construction.